A new human adipocyte model with PTEN haploinsufficiency. (1st January 2020) - Kässner, Franziska; Kirstein, Anna; Händel, Norman; Schmid, Gordian L.; Landgraf, Kathrin; Berthold, Antje; Tannert, Astrid; Schaefer, Michael; Wabitsch, Martin; Kiess, Wieland; Körner, Antje; Garten, Antje
ABSTRACT: Few human cell strains are suitable and readily available as in vitro adipocyte models. We used resected lipoma tissue from a patient with germline phosphatase and tensin homolog (PTEN) haploinsufficiency to establish a preadipocyte cell strain termed LipPD1 and aimed to characterize cellular functions and signalling pathway alterations in comparison to the established adipocyte model Simpson-Golabi-Behmel-Syndrome (SGBS) and to primary stromal-vascular fraction cells. We found that both cellular life span and the capacity for adipocyte differentiation as well as adipocyte-specific functions were preserved in LipPD1 and comparable to SGBS adipocytes. Basal and growth factor-stimulated activation of the PI3 K/AKT signalling pathway was increased in LipPD1 preadipocytes, corresponding to reduced PTEN levels in comparison to SGBS cells. Altogether, LipPD1 cells are a novel primary cell model with a defined genetic lesion suitable for the study of adipocyte biology.